Diabetes Mellitus and Hyperglycemia in Patients with Rheumatoid Arthritis (Texas Journal of Medical Science, 2022)
Proinflammatory cytokines involved in the pathogenesis of rheumatoid arthritis (RA) can inhibit insulin production and cause insulin resistance of peripheral tissues. Perhaps, with RA, the risk of developing disorders of carbohydrate metabolism (NUO) increases: diabetes mellitus (DM), fasting hyperglycemia (GN), glucose tolerance disorders. Patients with a combination of RA and DM belong to the category of the most severe patients with an unfavorable prognosis of macro- and microvascular complications. The problem of rheumatoid arthritis (RA) is becoming of general medical importance, since it creates prerequisites for improving the pharmacotherapy of other chronic diseases, such as atherosclerosis, diabetes mellitus (DM) type 2, osteoporosis, the development of which is also associated with chronic inflammation. The study of the pathogenesis of RA has revealed numerous "non-rheumatological" functions of proinflammatory cytokines, for example, the ability to interfere with various stages of metabolism glucose. It has been shown that tumor necrosis factor (TNF) α and interleukin (IL) 6 disrupt the synthesis and functioning of insulin receptors and intracellular glucose transporter in muscles, adipose tissue, liver, along with IL1ß inhibit insulin secretion, cause apoptosis of beta cells of islets Langerhans of the pancreas. RA can be considered as a model for studying disorders of carbohydrate metabolism (NUO). Several studies in RA patients have demonstrated a decrease in the level of functional capabilities of β-cells and an increase in insulin resistance of peripheral tissues. Rheumatoid arthritis (RA) is an immuno-inflammatory disease characterized by chronic erosive arthritis and systemic damage to internal organs, which leads to an increased risk of concomitant pathology, early disability and a decrease in the life expectancy of patients.